Prognostic significance of inflammatory biomarkers in diabetic and non-diabetic patients with STEMI, treated with primary percutaneous coronary intervention - Milić Veljko; Džudović Boris; Obradović Slobodan (Vojnosanitetski Pregled)
Background/Aim. Although the prognostic significance of inflammatory biomarkers, C-reactive protein (CRP) and fibrinogen, in the patients with the ST-segment elevation myocardial infarction (STEMI) is already known, the specific difference between such patients according to diabetic status remains unknown. Methods. The study was conducted in a single tertiary center. The values of CRP and fibrinogen were measured during the first 48 h in consecutive patients with first STEMI treated with primary percutaneous coronary intervention (pPCI). The patients were divided into two groups: with diabetes and without diabetes. The aim of this study was to determine a prognostic significance of maximal values of these two inflammatory biomarkers for in-hospital and six-month mortality in these two groups. Results. Among 475 patients, 126 (26.5%) were with diabetes and 349 (73.5%) were without diabetes. The patients with diabetes had significantly higher median values of CRP and fibrinogen compared to the nondiabetic patients [29.6 (10.4–91.8) mg/L vs 22.4 (9.79–49.2) mg/L, p = 0.046 and 4.7 (3.6–6.3) g/L vs 4.3 (3.6–5.4) g/L, p = 0.026, respectively]. However, the multivariate survival analysis using the Cox regression model showed that in the nondiabetic STEMI patients CRP and fibrinogen had significant prognostic value for in-hospital mortality [hazard ratio (HR) = 1.013, 95% confidence interval (CI) (1.004–1.022), p = 0.004; HR = 1.529 (1.023–2.287), p = 0.039, respectively]. Regarding six-month mortality, no significant difference was achieved. Overall survival was the lowest in the fourth quartile of CRP in the patients without diabetes. Conclusion. The higher values of CRP are the significant independent predictor of in-hospital and overall mortality in the STEMI patients without diabetes treated with primary PCI. Fibrinogen can also be used as an additional prognostic inflammatory biomarker for in-hospital mortality in the non-diabetics with STEMI.